REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN PHET SIMULATION TENTANG MATERI RANGKAIAN LISTRIK ARUS SEARAH SMA - Fungkar, Viter; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effectiveness of PhET Simulation Circuit Contruction kit media to remediate misconceptions of grade XII students of Senior High School. St. Benedict Pahauman on the material of direct current electric circuit. The method used is pre experimental design with one group pretest posttest design. Data taken from the students of class XII IPA 2 selected by intact group. The sample is 33 students. The data collection tool consists of 10 multiple choice questions with three alternative answers with an open reason. Based on data analysis, the highest student misconception profile was obtained when the pre-test was obtained (97%). The highest student misconception profile at the time of post-test was obtained (78,78%). Based on the calculation of the McNemar test, the mean of X ^ 2 count (6,249)> X ^ 2tabel (3,84) for db = 1 and Î± = 5% then there is a significant change of conception. Based on the calculation of effect size obtained score 0.4574 (moderate category) that remediation using PhET Simulation effective to remediate student misconception about material direct current electric circuit. This research is expected to be an alternative for teachers in implementing remediation to overcome student misconception.Keywords: Remediation, Misconception, PhET Simulation, Circuit Construction Kit, Direct Curren Electric Circuit.